MEKK1 Regulates Chemokine Expression in Mammary Fibroblasts: Implications for the Breast Tumor Microenvironment - Gentile, Saverio; Eskandari, Najmeh; Rieger, Michael A.; Cuevas, Bruce D. (Frontiers in Oncology, 2021)
Breast tumors contain both transformed epithelial cells and non-transformed stroma cells producing secreted factors that can promote metastasis. Previously, we demonstrated that the kinase MEKK1 regulates cell migration and gene expression, and that transgene-induced breast tumor metastasis is markedly inhibited in MEKK1-deficient mice. In this report, we examined the role of MEKK1 in stroma cell gene expression and the consequent effect on breast tumor cell function. Using a heterotypic cell system to quantify the effect of stroma cells on breast tumor cell function, we discovered that MEKK1-/- fibroblasts are significantly less effective at inducing tumor cell invasion than MEKK1+/+ fibroblasts. Expression array analysis revealed that both baseline and tumor cell-induced expression of the chemokines CCL3, CCL4, and CCL5 were markedly reduced in MEKK1-/- mammary fibroblasts. By focusing on the role of MEKK1 in CCL5 regulation, we discovered that MEKK1 kinase activity promotes CCL5 expression, and inactive mutant MEKK1 strongly inhibits CCL5 transcription. CCL5 and the other MEKK1-dependent chemokines are ligands for the GPCR CCR5, and we show that the CCR5 antagonist Maraviroc strongly inhibits fibroblast-induced tumor cell migration. Finally, we report that fibroblast growth factor 5 (FGF-5) is secreted by MDA-MB 231 cells, that FGF-5 activates MEKK1 effectors ERK1/2 and NFB in fibroblasts, and that chemical inhibition of NFB inhibits CCL5 expression. Our results suggest that MEKK1 contributes to the formation of a breast tumor microenvironment that supports metastasis by promoting expression of stroma cell chemokine genes in response to tumor cell-induced paracrine signaling.